PENGARUH PENAMBAHAN LIMBAH KAYU TERHADAP KARAKTERISTIK FISIK DAN MEKANIK MORTAR SEBAGAI MATERIAL KONSTRUKSI BERKELANJUTAN: PENGARUH PENAMBAHAN LIMBAH KAYU TERHADAP KARAKTERISTIK FISIK DAN MEKANIK MORTAR SEBAGAI MATERIAL KONSTRUKSI BERKELANJUTAN - Nor Puji Lestari; Vemi Widoanindyawati; Dianita Ratna Kusumastuti; Triwardaya; Marsudi (Bangun Rekaprima, 2026)
The utilization of wood waste as an additive in mortar has attracted increasing attention as an environmentally friendly approach to reducing industrial waste while promoting sustainable construction materials. This study aimed to evaluate the effect of wood waste addition on the physical and mechanical properties of mortar, particularly its early-age compressive strength. Wood waste was incorporated into the mortar mixture at proportions of 0% (control), 10%, and 15% by weight of fine aggregate. The tests included measurements of mass, density, and compressive strength of cube mortar specimens at the age of 3 days. The 3-day testing period was selected to evaluate the early-age characteristics of the mortar as an indicator of its initial physical and mechanical performance. The results revealed that increasing the wood waste content reduced the mass, density, and compressive strength of the mortar. The control mortar achieved an average compressive strength of 1.07 N/mm², whereas the incorporation of 10% and 15% wood waste resulted in strength reductions of approximately 31% and 66%, respectively. This reduction was mainly attributed to the low density, porous structure, and hygroscopic nature of wood waste, which increased mortar porosity, reduced the effective water available for cement hydration, and weakened the interfacial transition zone between the cement paste and wood particles. At higher wood waste contents, several specimens experienced premature failure during the compression test, indicating reduced structural integrity. Despite the reduction in compressive strength, the incorporation of wood waste decreased the density of the mortar, indicating its potential for producing lightweight mortar. Therefore, wood-waste mortar is more suitable for non-structural applications, such as masonry and plastering, while simultaneously supporting sustainable construction through the beneficial utilization of industrial wood waste